HOME CARE ON THE AN INCREASING NUTRITIONAL STATUS FOR THE CHILDREN UNDER FIVE IN YOGYAKARTA - Titih Huriah; Ema Waliyanti; Hanjayadi Hanjayadi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. Prevalence of children under five with malnutrition is an indicator of Millenium Development Goals (MDGs) that should be reach in a region (Regency/City) in 2015. Prevalence of nutrition base on weight for height (WFH) in Daerah Istimewa Yogyakarta showed that children under five prevalence with very lean nutrition status was about 2,6 percent and lean about 6,5 percent. Community Therapeutic Care combining three approaches to handling under five malnutrition children including community intervention, home based treatment for under five malnutrition children without complication and stabilitation center for under five malnutrition children with complication. The aim of this research was to find out the changing of malnutrition children under five through home care program in Yogyakarta. Method. This research used quantitative method through home care intervention for children under five with malnutrition and was conducted by nurse in public health center. Design of this research was pretest-posttest control group design. The population of this research was all children under five with malnutrition or not complication. Sample divided into two groups, 35 children for the intervention group and 25 children for control group. Analysis used was Paired t-test and independent t-test. Results. The result showed that before home care intervention, there is no significant difference of two groups. The result after intervention for three month with 7 times of visiting, home care intervention can increase nutritional status of children under five with malnutrition. The value of Independent t-test for control group and intervention group was significant with p<0,05. Discussion. The researcher conclude that Home Care has effect to increase nutrition status of children under five with malnutrition and also Z score value which is weight for height (WFH) was increase. Keywords: Home Care, Nutrition status , Malnutrition.